Physio-ecological responses of Patagonian coastal marine phytoplankton in a scenario of global change: Role of acidification, nutrients and solar UVR - Villafañe, Virginia Estela (2015)
The aim of our study was to experimentally determine the future combined effects of solar UVR (280–400 nm), nutrient enrichment and acidification on a natural phytoplankton community (late phase of the bloom) of the Chubut River estuary (Patagonia, Argentina). We exposed the community to two radiation conditions (i.e., with and without UVR) under a future scenario of global change as compared to present conditions, using a cluster environmental approach. We combined short- (hours) and mid-term (days) incubations under solar radiation of the two clusters (present vs. future) to focus on changes in phytoplankton photosynthesis, growth and biodiversity. Our results indicate that the future conditions of increased nutrient availability and acidification, together with solar radiation, would shape the coastal phytoplankton community of Patagonia. The observed change for future conditions was towards a community dominated by relatively large diatoms, with high growth rates, little or no UVR-inhibition of photosynthesis, and better light-utilization efficiency. Given the species-specificity in responses, our results should not be generalized, especially considering that open waters of Patagonia are characterized by recurrent blooms of coccolithophorids that could be severely affected by acidification process. This future global change scenario in coastal waters, however, will produce significant increases in primary production, with phytoplankton communities that may sequester significant carbon amounts and thus they might sustain important secondary production (including fisheries) if their nutritional quality is not compromised.